Investigation of the expedience of modification of the carbohydrate composition of rice flour in the technology of gluten-free bread - Medvid, Irina; Dotsenko, Viktor; Shydlovska, Olena; Ishchenko, Tatiana (My University, 2019)
The research considers a possibility of using modification of the carbohydrate composition of rice flour in the technology of bread of the special destination for celiachia. There has been conducted an analysis of the condition of the carbohydrate-amylase complex of rice flour. Revealed regularities have demonstrated that this flour has an unessential amylolytic activity that negatively influences the course of microbiological processes in gluten-free dough and quality parameters of ready products. The aim of the research was to develop arrangements as to accumulation of sugars in dough at the expanse of own reserves of rice bread for providing the necessary intensity of rice dough fermentation by using enzymes of the amylolytic effect. It is a precondition for improving structural-mechanical and organoleptic properties of gluten-free rice bread. At the same time accumulation of products of incomplete hydrolysis of flour starch in the process of its fermentative modification – dextrins will favor deceleration of ready products staling. There has been established the influence of α-amylase of the fungal origin and glucoamylase on accumulation of sugars at hydrolysis of rice flour starch. It has been studied, that dosage of α-amylase in amount 0,005 % and glucoamylase – 0,03 % of a flour mass results in creating sugars in amount 5,5–6 %. There has been proved the effectiveness of using α-amylase by accumulation of dextrins, in which composition the essential raise of the content of low-molecular ones – archo- and maltodextrins has been determined. Based on the conducted studies, it has been determined, that hydrolysis products of rice flour starch are created as a result of its fermentative modification by α-amylase and glycoamylase that is testified by the increase of gas-creation and acid-accumulation. There has been observed the positive influence of using modification of the carbohydrate composition of flour in the technology of rice bread on the specific volume, porosity structure and flexible-elastic properties of crumb of ready products. It has been established, that realization of hydrolysis of flour starch at producing rice bread favors prolongation of its fresh storage term as a result of raising the amount of dextrins, created under the effect of α-amylase. В дослідженні розглянуто можливість застосування модифікації вуглеводного складу рисового борошна в технології хліба спеціального призначення для хворих на целіакію. Проведено аналіз стану вуглеводно-амілазного комплексу рисового борошна. Виявлені закономірності показали, що дане борошно має незначну амілолітичну активність, що негативно впливатиме на перебіг мікробіологічних процесів у безглютеновому тісті та показники якості готових виробів. Метою наукової роботи було розроблення заходів щодо накопичення цукрів у тісті за рахунок власних резервів рисового борошна для забезпечення необхідної інтенсивності бродіння рисового тіста шляхом використання ферментів амілолітичної дії. Це являється передумовою покращення структурно-механічних та органолептичних властивостей безглютенового рисового хліба. Крім цього, накопичення в процесі ферментативної модифікації крохмалю борошна продуктів його неповного гідролізу – декстринів, сприятиме уповільненню черствіння готових виробів. Встановлено вплив α-амілази грибного походження та глюкоамілази на накопичення цукрів під час гідролізу крохмалю рисового борошна. Досліджено, що дозування α-амілази в кількості 0,005 % та глюкоамілази – 0,03 % до маси борошна призводить до утворення цукрів в кількості 5,5–6 %. Доведено ефективність застосування α-амілази за накопиченням декстринів, в складі яких визначено значне підвищення вмісту низькомолекулярних – ахро- і мальтодекстринів. На основі проведених досліджень визначено, що продукти гідролізу крохмалю рисового борошна, утворені внаслідок його ферментативної модифікації α-амілазою та глюкоамілазою, а саме моно- та дисахариди, інтенсифікують процес бродіння тіста, про що свідчить покращення газоутворення та кислотонакопичення. Відмічено позитивний вплив застосування модифікації вуглеводного складу борошна в технології рисового хліба на питомий об’єм, структуру пористості та пружно-еластичні властивості м’якушки готових виробів. Встановлено, що проведення гідролізу крохмалю борошна при виробництві рисового хліба сприяє подовженню терміну зберігання його свіжості, внаслідок підвищення кількості декстринів, утворених під дією α-амілази.
Keywords: celiachia; gluten-free bread; rice flour; α-amylase; glycoamylase; целіакія; безглютеновий хліб; рисове борошно; α-амілаза; глюкоамілаза; кафедра готельно-ресторанної справи